Shear zone softening at the base of the Cape Smith Belt: implications for the rheological evolution of thrust belts - Lucas, S.; St-onge, M. (Geoscience Canada, 1989)
Summary The rheological and structural consequences of thrust belt metamorphism have been studied using both numerical thermalrheological models and field and thin-section observations on ductile thrust zones in the Early Proterozoic Cape Smith Thrust Belt. Development of these ductile thrust zones had several important consequences for the evolution of the thrust belt: (1) penetrative bulk shear deformation of both hanging wall and footwall units leading to the development of mylonitic foliations; and (2) movement on a restricted number of relatively large displacement thrusts. Relatively broad ductile shear zones developed adjacent to thrusts during prograde metamorphism in order to accommodate movement on the thrusts, while relatively narrow shearzones developed adjacent to thrusts during retrograde metamorphism. The results of both the field studies and the thermal-rheological models suggest that temperature- (and time-) dependent weakening processes are strongly accentuated by lithological contrasts.